2002
DOI: 10.1002/cyto.10123
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of phagosomal pH of normal and CGD‐like human neutrophils by dual fluorescence flow cytometry

Abstract: Background: Phagosomal pH is thought to play an important role in the antimicrobial activity of polymorphonuclear leukocytes (PMNs). In this study, we set up a method for a rapid and accurate measurement of phagosomal pH in PMNs with the use of Candida albicans doubly labeled with a pH-insensitive and a pH-sensitive probe and flow cytometry. Methods: Heat-killed, serum-opsonized C. albicans were doubly labeled with fluorescein, a pH-sensitive probe, and rhodamine, a pH-insensitive probe, and incubated with hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…In the present study, however, DPI treatment of Trpm2 −/− mBMDMs failed to alter significantly phagosomal pH, indicating that the increased pH seen in Trpm2 −/− mBMDMs was caused by TRPM2 deletion rather than increased ROS production secondary to TRPM2 deletion (Di et al, 2011). Thus, the dysregulated phagosomal pH in Trpm2 −/− BMDMs, as opposed to the overproduction of ROS, was essential for the phagosomal killing of bacteria as was shown to be the case for CDG neutrophils (Dri et al, 2002;Geiszt et al, 2001;Henriet et al, 2013;Segal et al, 1981;Thrasher and Segal, 2011).…”
Section: (N=3) *P<005 (T-test) (Fg) Adpr Antagonism Increases Phasupporting
confidence: 39%
See 1 more Smart Citation
“…In the present study, however, DPI treatment of Trpm2 −/− mBMDMs failed to alter significantly phagosomal pH, indicating that the increased pH seen in Trpm2 −/− mBMDMs was caused by TRPM2 deletion rather than increased ROS production secondary to TRPM2 deletion (Di et al, 2011). Thus, the dysregulated phagosomal pH in Trpm2 −/− BMDMs, as opposed to the overproduction of ROS, was essential for the phagosomal killing of bacteria as was shown to be the case for CDG neutrophils (Dri et al, 2002;Geiszt et al, 2001;Henriet et al, 2013;Segal et al, 1981;Thrasher and Segal, 2011).…”
Section: (N=3) *P<005 (T-test) (Fg) Adpr Antagonism Increases Phasupporting
confidence: 39%
“…The role of the ROS and NOX pathway in intra-phagosomal bacterial killing has been proposed in part based on findings in chronic granulomatous disease (CGD) (Pollock et al, 1995;Segal, 1996;Segal et al, 2000). CDG is characterized by severe, protracted and fatal infection resulting from the failure of the NOX system to produce superoxide (O 2 − ) and other ROS in neutrophils (Pollock et al, 1995;Segal, 1996;Segal et al, 2000); however, it was later discovered that defective bacterial killing in CGD neutrophils was secondary to dysregulated phagosomal acidification mechanism (Dri et al, 2002;Geiszt et al, 2001;Henriet et al, 2013;Segal et al, 1981;Thrasher and Segal, 2011). We previously showed that TRPM2 inhibited NOX-mediated ROS generation, specifically that there was overproduction of ROS in Trpm2 −/− macrophages infected with E. coli (Di et al, 2011).…”
Section: (N=3) *P<005 (T-test) (Fg) Adpr Antagonism Increases Phamentioning
confidence: 99%
“…It has been reported that the phagosomal pH undergoes a biphasic change, that is a quick and short lasting alkalinization (nearly to pH 7.6) followed by a slower acidification (nearly to pH 6.5) (26,28). Although the fluorescein green emission is expected to decrease at acidic pH (see reference 6 and references cited therein), under our experimental conditions such a decrease, if occurs, does not seem to interfere with the 5(6)-FAM-SE green fluorescence of ingested C. albicans particles.…”
Section: Discussionmentioning
confidence: 99%
“…albicans cells, obtained from a clinical isolate from the microbiology laboratory of the pediatric hospital IRCCS Burlo Garofolo (Trieste, Italy), were grown in Sabouraud dextrose broth at 30°C for 18 -20 h. Labeling was performed according to the method described by Dri et al (26), with slight modifications. After growing, yeast cells were washed twice at 2,000g for 7 min in physiologic saline and heat killed by boiling for 10 min.…”
Section: Opsonization and Labeling Of C Albicansmentioning
confidence: 99%
“…Labeling of C. albicans blastospores was performed according to the method described by Dri et al (29), with slight modifications. Serumopsonized yeast particles were diluted in NaHCO 3 buffer (0.1 M, pH 8.3), washed and suspended in the same medium (300 ϫ 10 6 /ml) containing 1.5 g/ml 5(6)-FAM-SE to start labeling.…”
Section: Labeling Of C Albicansmentioning
confidence: 99%